The role of transposable elements in the ecological morphogenesis under the influence of stress - R. N. Mustafin; E. K. Khusnutdinova (Вавиловский журнал генетики и селекции, 2019)
In natural selection, insertional mutagenesis is an important source of genome variability. Transposons are sensors of environmental stress effects, which contribute to adaptation and speciation. These effects are due to changes in the mechanisms of morphogenesis, since transposons contain regulatory sequences that have cis and trans effects on specific protein-coding genes. In variability of genomes, the horizontal transfer of transposons plays an important role, because it contributes to changing the composition of transposons and the acquisition of new properties. Transposons are capable of site-specific transpositions, which lead to the activation of stress response genes. Transposons are sources of non-coding RNA, transcription factors binding sites and protein-coding genes due to domestication, exonization, and duplication. These genes contain nucleotide sequences that interact with non-coding RNAs processed from transposons transcripts, and therefore they are under the control of epigenetic regulatory networks involving transposons. Therefore, inherited features of the location and composition of transposons, along with a change in the phenotype, play an important role in the characteristics of responding to a variety of environmental stressors. This is the basis for the selection and survival of organisms with a specific composition and arrangement of transposons that contribute to adaptation under certain environmental conditions. In evolution, the capability to transpose into specific genome sites, regulate gene expression, and interact with transcription factors, along with the ability to respond to stressors, is the basis for rapid variability and speciation by altering the regulation of ontogenesis. The review presents evidence of tissue-specific and stage-specific features of transposon activation and their role in the regulation of cell differentiation to confirm their role in ecological morphogenesis.